'Okres Poznański' w Twórczości Romana Suszki - Pogonowski, Jerzy (Investigationes Linguisticae, 2007)
We discuss the scientific achievements of one of the most prominent Polish logicians of the 20th century - ROMAN SUSZKO in the period when he was active at the University in Poznań (1946 - 1953), i.e. at the very beginning of his academic career.